Prisoners’ Rights in India: A Human Rights Perspective - Kaur, Richa (Christ University Law Journal, 2025)
The most significant document pertaining to prisoner’s rights are the Standard Minimum Rules for the Treatment of Prisoners (presently titled as Nelson Mandela Rules). As far as prisoners’ rights in India is concerned, the Constitution does not explicitly mention about their rights, but the judiciary has been instrumental in protecting the rights of prisoners by giving a liberal interpretation to Article 21 of the Constitution to include their rights within the ambit of the provision. The Model Prison Manual, 2016 and Model Prisons and Correctional Services Act, 2023 have been drafted by the government to give impetus to prison reforms and effectively implement the Nelson Mandela Rules in India. Despite the dominance of India in the economic and democratic front globally, it is fraught with an ineffective adjudication process in its criminal justice system resulting in denial of rights to the accused. The paper delves into the legal framework that governs human rights of prisoner vis-à-vis under trial prisoners in jails along with the predicaments of undertrials. It analyses the secondary data sources that include Prison Statistics Report- 2022, newspaper reports as well as information from digital platforms like the National Judicial Data Grid (NJDG) and National Prison Portal (NPP) to augment the study. Furthermore, from data collected through the Right to Information Act, 2005 it seeks to provide an insight into the lacunae in the Indian criminal justice system as it fails f to provide respite to under trials, with respect to grant of bail sans conviction by a court of law.